2020
DOI: 10.1186/s12902-020-0490-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characterization of patients with primary aldosteronism plus subclinical Cushing’s syndrome

Abstract: Background: Primary aldosteronism (PA) plus subclinical Cushing's syndrome (SCS), PASCS, has occasionally been reported. We aimed to clinically characterize patients with PASCS who are poorly profiled. Methods: A population-based, retrospective, single-center, observational study was conducted in 71 patients (age, 58.2 ± 11.2 years; 24 males and 47 females) who developed PA (n = 45), SCS (n = 12), or PASCS (n = 14). The main outcome measures were the proportion of patients with diabetes mellitus (DM), serum po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…SCS is generally found when a patient with an unidentified adrenal mass underwent DMST, and it is the most common endocrine syndrome associated with an adrenal adenoma ( 22 , 24 ). Many cases of PA with SCS have been reported as aldosterone/cortisol cosecreting adenomas ( 6 ). Both overt and subclinical Cushing's syndrome develop hypertension, dyslipidemia, insulin resistance and T 2 DM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SCS is generally found when a patient with an unidentified adrenal mass underwent DMST, and it is the most common endocrine syndrome associated with an adrenal adenoma ( 22 , 24 ). Many cases of PA with SCS have been reported as aldosterone/cortisol cosecreting adenomas ( 6 ). Both overt and subclinical Cushing's syndrome develop hypertension, dyslipidemia, insulin resistance and T 2 DM.…”
Section: Discussionmentioning
confidence: 99%
“…SCS could cause hypertension, insulin resistance, and dyslipidemia ( 5 ). The coexisting PA and SCS are associated with increased cardiovascular morbidity and mortality ( 6 ). Previous studies have shown that the incidences of coexistent PA and SCS range between approximately 10 and 20% ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The size of the aldosterone‐producing adenoma matters for the identification of subclinical Cushing's syndrome 9,10 . Such patients all had large (2.0‐2.5 cm in diameter) adenomas, minimally 1.1 cm 12 . Adenomas are usually in a single neoplasm that secrets both aldosterone and cortisol, but can also be in two different neoplasms, either ipsilateral or contralateral, that secret aldosterone and cortisol, respectively 9 .…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 10 Such patients all had large (2.0‐2.5 cm in diameter) adenomas, minimally 1.1 cm. 12 Adenomas are usually in a single neoplasm that secrets both aldosterone and cortisol, but can also be in two different neoplasms, either ipsilateral or contralateral, that secret aldosterone and cortisol, respectively. 9 If the diameter of the aldosterone‐producing adenoma is 2.0‐2.5 cm, subclinical Cushing's syndrome has to be considered.…”
Section: Discussionmentioning
confidence: 99%